News: the politics of illusion - Bennett, W. Lance (New york: Addison wesley logman, 2001)
Contents: C 1.- an introduction to the news about people, society, and politics. C 2.- news content: four information bases that matter. C 3. the social, economic, and political construction of news reality. C 4.- how politicians make the news. C 5.- how journalists report the news. C 6.- inside the profession: objectivity and other double standards. C 7.- the public: prisioners of the news. C 8.- freedom from the press: solutions for concerned citizens.
Keywords: Comunicación Social